De-Industrialization: concept, causes, effects and the Brazilian case. - Oreiro, José Luis; Feijó, Carmem A. (Brazilian Journal of Political Economy, 2010)
This article aims to do a theoretical discussion about the term “de-industrialization” and its relationship with other concepts as “primarization” of exports and “Dutch disease”. After that we will analyze the possible causes and effects of “de-industrialization”. Finally, we analyze the Brazilian case, with a special attention over the economic literature about this issue. JEL Classification: L6; O14; O54.